Evaluation of effectiveness of locking compression plates in internal fixation of proximal humerus fractures: a prospective study (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Locking compression plate (LCP) provides significant biological and biomechanical advantages in the management of proximal humerus fracture (PHF) by providing greater stability, vascular preservation, superior healing, and fewer complications. However, the translation of these properties to functional benefits for patients remains to be elucidated. The objective of the study was to evaluate the effectiveness of LCP in internal fixation of PHF in terms of rate of healing and functional outcomes.Method: This prospective study enrolled 30 Proximal Humerus Fracture patients aged >18 years, from both genders, and treated them with LCP. They were followed up regularly for 1 year and assessed clinically and radiologically using Neer’s criteria and Constant-Murray score. Results were analysed using Chi-square test, p≤0.05 indicated statistical significance.Result: With a mean age of 45.20±15.02 y and M:F ratio of 2.3:1, most patients showed right-sided injuries 18(60%) and Neer 4-part injuries 13(43.33%), predominantly due to road traffic accidents 19(60%), with a satisfactory Neer’s score 26(86.67%) and a good Constant-Murray score 16(53.33%).  The mode of injury showed significant association with age (p=0.013) but not with gender (p=0.866). Over follow up, 27(90%) patients maintained humeral head height and 24(80%) patients showed good humeral neck-shaft angle. Radiological union of PHF took 12 weeks in 12(43.33%) of patients with no dislocation in 27(90%) of patients. However, 1(3.3%) patient showed no union.Conclusion: LCP is associated with favorable clinical, functional and radiological outcomes in PHF patients by providing rapid healing and good rigidity, angular stability, and torsional strength.